Nonunions Diagnosis, Evaluation and Management (Springer US, 2018)
Providing a comprehensive presentation of the diagnosis, evaluation and management of nonunions, this generously illustrated text details the current principles, surgical techniques and approaches with these challenging clinical situations. Since each nonunion can be fairly particular, the treatment regimens provide guidelines to effectively approach such problems. Opening with a discussion of the principles of nonunions and fracture healing, the remainder of the book is divided by anatomical area and provides evidence-based recommendations, case examples, and preferred treatment/algorithms for both the upper and lower extremities, including the clavicle, the proximal humerus, proximal femur, and tibial plateau, as well as the pelvis and acetabulum. Specialized circumstances are also discussed, including periprosthetics and joint replacement. Although not every single treatment option is described for every sin gle anatomical area and type of injury, Nonunions is an excellent resource for orthopedic trauma surgeons, residents and students, not only for managing these common yet complex problems but also in preventing nonunions from occurring by avoiding surgical causes and mitigating patient risk factors. . .